Understanding Domestic Workers Protection & Welfare Policy and Evaluating its Applications to Managing Human Resources of Informal Sector in Bangladesh - Islam, Mohammad Shariful; Al Amin, Md. (Journal of Asian Business Strategy, 2017)
The aim of this article is to give insights on Domestic Workers Protection and Welfare Policy (DWPWP)-2015 of Bangladesh. It also studied the level of application of the policy and awareness. The methodology of the article is both quantitative and qualitative. In view to evaluate application level, a structured questionnaire has been executed among 150 families of Dhaka City. All respondents are from household family as a key stakeholder. Each set consist of 12 specific questions in accordance with the key provision of the policy. Responses from all families have properly and adequately received. The finding shows that 80% of employers are complying pre-negotiations and fixation of workers salary, provided leave and recreation facilities as per employment condition. In other findings, poor media coverage, Illiteracy of workers, poverty of workers, supports of the social community, Absence of basic awareness course are most important factors behind the lack of awareness about the policy and its applications. Descriptive statistical tools i.e. percentile methods, mean, standard deviations used to show the scenario of application of the policy. Finally, efforts have been given to align the subject matter of the policy with core functions and perspectives of human resources management with identification of some problems and recommendations.